Biopreservação de filés resfriados de Oreochromis niloticus (tilápia-do-nilo) com compostos antimicrobianos de bactérias ácido-láticas - Carli, Rodrigo Cavalheiro (2022)
The tilapia fillet, the most cultivated fish in the world, due to additional handling, is subject to enzymatic and microbial deterioration - mainly by psychrotrophic bacteria - causing organoleptic changes and decreasing the acceptability of the product by consumers. The search for efficient conservation methods that preserve freshness is necessary to guarantee the population's access to this product of high nutritional value. However, due to the change in the profile of the modern consumer by the search for foods that do not undergo aggressive conservation processes - not to change the characteristics of the product - that do not contain chemical additives and that remain fresh for as long as possible, biological methods such as The use of bacteriocins used from Lactic Acid Bacteria (BALs) appears as an option. Therefore, an alternative method is proposed for the biopreservation of chilled Nile tilapia fillets through the use of BALs bacteriocins. The first stage of the work consisted of the evaluation of the shelf life of the fillet and the isolation of the deteriorating microorganisms, in the second stage the production, semi-purification of the bacteriocins and the evaluation of their inhibitory effect against the psychrotrophic microorganisms isolated from the first stage was performed to select the most effective compounds. In the third stage, bacteriocins were applied directly to the tilapia fillet to assess the impact on shelf life. The results demonstrate that the shelf life of the fillet cooled to 4 ° C is less than ten days, during isolation and bacterial identification, in addition, the initial contamination showed failures during the process of harvesting, slaughter or filleting. All isolates had the same biochemical characteristics, indicating that they are microorganisms of the same genus (Pseudomonas). In the antimicrobial sensitivity test, the crude and semi-purified extract of Lactobacillus salivarius showed inhibition compared to Pseudomonas spp. of Lactobacillus salivarius in fresh fish fillet results in increased shelf life from food.